Ajaran salah dan analisis ciri-ciri kesalahan yang difatwakan bertentangan dengan Ahl al-Sunnah Wa al-Jama’ah oleh Majlis Ugama Islam Brunei Darusalam / Matussein Haji Jumat - Matussein , Haji Jumat (2017)
Brunei Darussalam is not exempted from the issue of groups of minorities who have introduced various misleading teachings which, in return, contributes to the misunderstanding of the general public. In addition, such actions have even spurred some minorities to create their own groups and claim to spread the „teachings of Islam‟. Eventually, these teachings are condemned as deviant teachings by The Islamic Religious Council as the contents contradict the belief of Ahl al-Sunnah wa al-Jamā‘ah. Research on decreed errors that contradicts the Ahl al-Sunnah wa al-Jamā‘ah are considered to be paramount and seen as an urgency that ought to be undertaken by the scholars as part of the Sunnah of Rasūlullāh (S.A.W.). Although Brunei has gazetted fatwa against the deviant teachings, the argument against the offense committed has been entirely based solely on the thought of al-Ashā‘irah while neglecting the other thoughts that are inconsistent with it. Therefore, this study focuses on the primary objective, that is mainly to investigate the foundations practiced by Ahl al-Sunnah wa al-Jamā‘ah, as clarified by mufti of Brunei and religious scholars of the respected al-Ashā„irah, as well as to analyse and classify the teachings found in Brunei so that each characteristic may be based on the thought and teachings of al-Ashā‘irah. This will also serve to maintain the sustainability of the methodology of Ahl al-Sunnah wa al-Jamā‘ah which has been long practiced in Brunei. The methodology of the study based on descriptive studies in qualitative form. Data collecting methods are obtained from the informants from The Islamic Religious Council, The Akidah Security Section and the committees related to deviant teachings as well as the intermediate and secondary sources of library documentary materials. Data analysis is correlated to an inductive method that accommodates the incidents that have occured in Brunei, followed by deductive and comparative methods leading to concise formulas and conclusions. In this study, every decree has been enlightened in advance to see whether the ittifaq, or ikhtilaf, has become a new trend or have been repeatedly used in the deviant teachings before comparing it with al-Ashā‘irah. The findings show that only the Islamic Religious Council has the knowledge and authority to describe the decree or characteristics that oppose the teachings of Ahl al-Sunnah wa al-Jamā‘ah. Although the fatwa of The Islamic Religious Council concerned became merely as an „endorsement‟ to the fatwa of the Mufti States Departments which does not meet the production process requirements of the fatwa in the law of The Islamic Religious Council. Although the fatwa was gazetted to ban any religious group, but the decreed errors brought by an individual or group is less refined and understood if argued deeper. The study also found a rationale Ahl al-Sunnah wa al-Jamā‘ah to guide Brunei Darussalam is not updated. This indicates Brunei desperately needs a scholar of the faith or akidah in Brunei, especially those with the method of al-Ashā‘irah to confirm that the decreed or characteristics of the offense based on areas other than the faith and knowledge of al-Ashā‘irah as an action that does not conform to the teachings Ahl al-Sunnah wa al-Jamā‘ah. Therefore, measure to deal with any of the teachings depends heavily on fiqhiyyah methods ‘Sadd al-Dharā‘i’’ to replace the sharia court prosecution process and not to mention the weak enforcement which not successfully meet the requirements of the elements related to the teachings of Islam which is required in the proof. This study concludes that the argument aligned with al-Ashā‘irah thinking method, according to the areas involved in the handling of one, serves as a reference and guide in providing a description of the characteristics of the offenses or decreed errors in the fatwa that are considered to oppose the Ahl al-Sunnah wa al-Jamā‘ah in Brunei Darussalam.